Learning from Earthquakes: The Role of Socio-Scientific Issues in Developing Students’ Science Argumentation Skills - Atika Fatharani; Madlazim Madlazim; Mita Anggaryani; Muhammad Satriawan; Kiki Septaria (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to develop and test the effectiveness of learning modules based on Socio-Scientific Issues with Problem-Based Learning (SSI-PBL) approach in improving students' scientific argumentation skills on the topic of earthquake mitigation. The research method used is Research and Development with the 4D model (Define, Design, Develop, Disseminate) involving 95 grade VIII students at SMP Negeri 1 Maduran, Lamongan. Data collection techniques included scientific argumentation tests (pre-test and post-test), observation of student activities and learning implementation, and student response questionnaires. Data were analyzed descriptively quantitatively and inferentially using paired t-test, gain score and ANOVA test to measure skill improvement. The results showed a significant improvement in students' argumentation skills, with an average post-test score of 68% compared to 21% in the pre-test, as well as improvements in the indicators of claims (from 28% to 72%), use of data (15% to 65%), and preparation of rebuttal (25% to 58%). The SSI-PBL design facilitated deeper engagement by situating students in authentic, real-world contexts that required critical examination of seismic data, policy debates, and ethical considerations. These findings suggest that the SSI-PBL module is able to bridge the gap between theory and practice in disaster learning and strengthen 21st century skills such as critical thinking, problem solving, and public policy literacy. Results underscore the module’s effectiveness in fostering scientific literacy, critical thinking, and policy awareness, essential for disaster-resilient communities.